Kualitas Bakteri Asam Laktat Isolasi Jerami Padi Dengan Penambahan Berbagai Level Molases - Anwar Effendi Harahap (State Islamic University of Sultan Syarif Kasim Riau, 2017)
One of the problems in the development of ruminants, especially in the dry season is difficult to feed of quantity and quality. The aim of this research is to study of pH, the number of colonies of Lactic Acid Bacteria, antimicrobial isolated from rice straw silage with the addition of levels of molasses. This research was conducted from Juli until November 2015 at Laboratory of Agrosotology, Feed Industry and Soil Science, Faculty of Agriculture and Animal Science, State Islamic University of Sultan Syarif Kasim Riau.. The research method of rice straw silage with the addition of various levels of molasses, isolation of lactic acid bacteria and antimicrobial effect. The method used to analyze pH, the number of colonies of Lactic Acid Bacteria, and antimicrobial effect is exploration by using descriptive analysis. The conclusion that treatment of rice straw silage by adding molasses 9% level pH content, the number of colonies and the antimicrobial effect better than the other treatments.